Las artes plásticas en el desarrollo de la pinza digital en niños de 3 a 4 años del centro de educación inicial "Carlota Noboa de Durango", cantón Guaranda, provincia Bolívar, periodo 2024 - Asas Chimborazo, Ruth Jessenia (2025)
This research project examines the impact of the plastic arts on the development of the digital pincer in children from 3 to 4 years old at the Early Education Center “Carlota Noboa de Durango”, because the digital pincer is fundamental for fine motor skills, which allows holding small objects such as pencils, being crucial for the academic and autonomous development of children. With an applied methodology and a field research design, surveys to teachers and direct observation in the classroom were used, although the importance of plastic arts is recognized, the use of specific spaces and materials is limited. The results indicate that children actively participate in artistic activities, which favors their fine motor development, although areas that need more support are identified, and it is concluded that the implementation of fine arts in the curriculum should be strengthened, classroom resources should be optimized, methodologies should be updated and parental participation should be encouraged to enhance fine motor skills in early childhood, in addition this study offers a methodological guide applicable to other educational centers interested in improving these skills through fine arts